FAKTOR-FAKTOR PENYEBAB DAN DAMPAK SESEORANG BERMAIN JUDI TOGEL (TOTO GELAP) (Studi di Desa Bengkulu Rejo Kecamatan Gunung Labuhan Kabupaten Way Kanan) - Saputra, Asep; Syani, Abdul (SOCIOLOGIE, 2013)
This study aims to determine the cause of a persons gambling lottery, how it impacts experienced post players to play gambling toggle, and how the reality of the condition of the villagers of Bengkulu rejo with lottery gambling. This study uses qualitative methods. Collecting data using in-depth interview techniques. Determination of purposive sampling of informants by selecting some community members who are directly involved in game gambling lottery and some village leaders Bengkulu rejo devices. The results showed that: firstly, the tendency of actors to play gambling toggle caused social and economic factors, as well as followed by other causal factors, namely the situational factor, the curiosity factor, factor perception of skills, and perception of victory factor; second, impact experienced actors affect the familys economic, social, and psychological offender; third, safety and comfort of Bengkulu villagers rejo be disturbed.Keywords: Impact, gambling toggle